Vejrforholdene i Landbrugsaaret 1917—18. (Fra 1. Oktober 1917 til 30. September 1918.) - Hansen, H. (Tidsskrift for Landøkonomi, 2018)
Vejrforholdene i Landbrugsaaret 1917—18. (Fra 1. Oktober 1917 til 30. September 1918.)